The management of Heritage in rural areas: the case of Historic Celtiberia - Chordá, Marta; Cerdeño, María Luisa (Complutum, 2021)
The rural cultural heritage has the same problems found in other areas, but with an added problem: the oblivion; and so that, the abandon. However, in current crisis context this situation opens us a door for reflection and dynamization. To work on it. This happens in the rural inland, mainly in those areas which were the historic Celtiberia. Today those areas are the epicenter of the European depopulation. This is a real and serious socioeconomic problem, as well as an important vulnerability of the landscape. The rural cultural heritage is varied, archaeological, ethnographic, intangible and natural, but the lack of public investment together with the excess of expectations based on the joint of the tourism-heritage makes the current started projects non-viable. Analyzing the scientific and archaeological activity in rural areas through the lens of the Sustainable Development Goals would open again the doors to restart all these projects. This article analyzes the current situation of this heritage and its research and points out the threats and opportunities for the future.
Keywords: cultural heritage; celtiberian heritage; landscape; depopulation